A dual photoluminescence enhancement system: stabilization of a water soluble AIEE fluorogen using silver nanowire. (1st December 2016) - Chiang, Ying-Chen; Huang, Chun-Ta; Wang, Wei Hsin; Chang, Cheng-Chung
Abstract : This manuscript describes the preparation of water soluble aggregation-induced emission enhancement (AIEE)-based fluorescent organic nanoparticles (FONs). The fluorescence diversity of the FONs was investigated in the presence of silver nanowires. We observed that the emission of the FONs can be enhanced by mixing with the nanowires, which is believed to originate from resonance between the emission of the FONs and the surface plasmon resonances of the metal surface. That is, the AIEE phenomenon was promoted according to the metal-enhanced fluorescence (MEF) mechanism that can be used to build up a novel double emission enhancement (DEE) platform and to extend the range of AIEE applications. The systemic fluorescence enhancement, lifetime and photostability were measured and the AIEE–MEF evaluation and the interaction between the FONs and nanowires were discussed based on the obtained spectral data and SEM and fluorescent microscopy images.